Modifying the Replication of Geminiviral Vectors Reduces Cell Death and Enhances Expression of Biopharmaceutical Proteins in Nicotiana benthamiana Leaves - Diamos, Andrew G.; Mason, Hugh S. (Frontiers in Plant Science, 2019)
Plants are a promising platform to produce biopharmaceutical proteins, however the toxic nature of some proteins inhibits their accumulation. We previously created a replicating geminiviral expression system based on bean yellow dwarf virus (BeYDV) that enables very high-level production of recombinant proteins. To study the role of replication in this system, we generated vectors that allow separate and controlled expression of BeYDV Rep and RepA proteins. We show that the ratio of Rep and RepA strongly affects the efficiency of replication. Rep, RepA, and vector replication all elicit the plant hypersensitive response, resulting in cell death. We find that a modest reduction in expression of Rep and RepA reduces plant leaf cell death which, despite reducing the accumulation of viral replicons, increases target protein accumulation. A single nucleotide change in the 5’ untranslated region (UTR) reduced Rep/RepA expression, reduced cell death, and enhanced the production of monoclonal antibodies. We also find that replicating vectors achieve optimal expression with lower agrobacterium concentrations than nonreplicating vectors, further reducing cell death. Viral UTRs are also shown to contribute substantially to cell death, while a native plant-derived 5’ UTR does not.